Die Genitalien der paläarktischen Tineiden (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1958)
Group VI of the work on palaearctic Tineidae deals with the genus Euplocamus Latr., the systematic position of which is dubious. The species may be separated by external characters as well as by the male genitalia, while the female genitalia were found so similar that they could not be used for determination of species.